2013
DOI: 10.1108/17410391311289532
|View full text |Cite
|
Sign up to set email alerts
|

Operations research within UK healthcare: a review

Abstract: Purpose -The purpose of this paper is to identify the existing literature on the wide range of operations research (OR) studies applied to healthcare, and to classify studies based on application type and on the OR technique employed. The scope of the review is limited to studies which have been undertaken in the UK, and to papers published since the year 2000. Design/methodology/approach -In total, 142 high-quality journal and conference papers have been identified from ISI Web of Knowledge data base for revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Table 2 presents the remaning 16 reviews which present multiple types of applications and the classification of the applications of simulation studies, within those articles [7,8,12,14,16,18,20,22,25,27,28,33,34,36,37,39]. The numbers of simulation studies relating to the different application groups were identified and extracted from the sixteen reviews.…”
Section: Data Extraction 331 Types Of Applicationsmentioning
confidence: 99%
“…Table 2 presents the remaning 16 reviews which present multiple types of applications and the classification of the applications of simulation studies, within those articles [7,8,12,14,16,18,20,22,25,27,28,33,34,36,37,39]. The numbers of simulation studies relating to the different application groups were identified and extracted from the sixteen reviews.…”
Section: Data Extraction 331 Types Of Applicationsmentioning
confidence: 99%
“…Fakhimi and Mustafee (2012) suggested that combining Operations Research and Simulation techniques will reduce the limitations of individual methods and increase their capabilities. Few studies addressing this integration were reported in the fresh produce literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jun, Jacobson, and Swisher (1999) reviewed the modeling of healthcare systems, with an emphasis on Discrete-event Simulation, while Fone et al (2003) conducted a systematic review of the use of simulation modeling in population health. Fakhimi and Mustafee (2012) focused on UK healthcare modeling. A comprehensive review, which examined 342 articles based on nine criteria, was conducted by (Brailsford et al 2009).…”
Section: Introductionmentioning
confidence: 99%